Practicum Evaluation System (PES) / Cheong Tau Han … [et al.] - Tau Han, Cheong; Aperapar, Parmjit Singh; Sian Hoon, Teoh; Mohd Salleh, Noor Shah; Mohd Nasir, Nurul Akmal (Research Innovation Business Unit, 2014)
This project promotes green technology in assessing practicum students’ performance at the same time to reduce printing cost and administrative cost of Faculty of Education UiTM. A program named Practicum Evaluation System (PES) is developed, using C++ Language, in order to achieve the goal. The program is well designed and user friendly to be used. Previously practicum supervisor needs to fill in at least five different forms for each students and they have to calculate the total marks manually. With PES, supervisor just needs to enter students’ practicum marks and let PES do the calculation and report printing. Besides, PES does provide email function where supervisor has the option to print the report or send e-report to coordinator. Indirectly, this promotes green technology. Nevertheless, PES can easily generate appointment letter to respective supervisor to save administrative cost.